Propuesta de agroturismo para la finca Salinas de la parroquia Zurmi, cantón Nangaritza, provincia de Zamora Chinchipe - Castillo Gaona, Enith Andreina (2018)
In Ecuador, agritourism is a new activity that allows to revitalize the economy of the families of the rural sector, while creating sources of employment in the countryside. For its part Zamora Chinchipe as well as the Canton Nangaritza are places full of natural richness and therefore the property "Salinas" belonging to the parish Zurmi; It has several activities conducive to the development of agritourism and space available for the implementation of tourist services, that is why we see the need to carry out this research; "Proposal of Agritourism for the farm SALINAS of the parish ZURMI, canton NANGARITZA, province of ZAMORA CHINCHIPE". For the development of the research, a general objective was posed: "to elaborate a proposal of agritourism for the Salinas farm of the same parish, Nangaritza Canton, province of Zamora Chinchipe", likewise specific objectives were posed: to realize the Tourist diagnosis of the farm Salinas of the parish Zurmi, Canton Nangaritza, province of Zamora Chinchipe; In which it was possible to know the current situation of the farm both internal and external. Create a proposal for agritourism for the property Salinas, Zurmi parish, Nangaritza Canton, province of Zamora Chinchipe; Which was carried out by means of the definition of a technical study and the development of a workshop of socialization, allowing to obtain suggestions and recommendations for the development of the investigation. Inductive, deductive, analytical and descriptive methods were used; That was obtained, selected and analyzed the field information; In addition, the matrix of Carla Ricaurte Quijano and the inventory and summary sheets of the Ministry of Tourism were used; The techniques used were the interview and the direct observation, which allowed to develop the matrix SWOT (Strengths, weaknesses, , opportunities and threats) with which the strategies for elaborating the proposal could be established. The MARPP technique was also used for the correct socialization of the project. In terms of results, an internal and external analysis of the farm was carried out, in which it is possible to show that the same parish has great tourist potential to attract visitors in order to develop the agritourism in the "Salinas" farm, being the agritourism proposal A fundamental guide for the implementation of this activity and the insertion of the farm in the tourist area. After having done the work, it is concluded that the property "Salinas" has a great tourist potential because it has special characteristics to attract the visitors, which can be used for the tourist to enjoy the rural landscape and at the same time Live and perform the daily activities of the family living in the farm. Likewise, it is recommended to the owner of the farm to take into consideration the proposal of agritourism, as a guide to start the agritourism activity in his farm, using the strategies of publicity and diffusion, in the same way to innovate the activities and Services to offer. It is also recommended to the owner of the farm to take advantage of the products that are given within this one to carry out in a continuous way, for example the canned goods and marmalade of guava and pineapple, thus obtaining more economic benefits.